2018
DOI: 10.21831/reid.v4i2.22218
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of physics problem-solving skills of senior high school students using PhysProSS-CAT

Abstract: Evaluation using computerized adaptive tests (CAT) is an alternative to paper-based tests (PBT). This study was aimed at mapping physics problem-solving skills using PhysProSS-CAT on the basis of the item response theory (IRT). The study was conducted inSleman Regency, Yogyakarta, involving 156 students of Grade XI of senior high school. Sampling was done using stratified random sampling technique. The results of the study show that the PhysProSS-CAT is able to accurately measure physics problem-solving skills… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
3
4
0
Order By: Relevance
“…They do not get the concept. It is in line with [4], [9] about the physics test higher order thinking skills development, stated that students creative thinking was categorized as poor. This study aimed to determine the increase in students' higher order thinking skills (HOTS) in physics learning and how the effect of using Synectic learning models on physics learning in high school.…”
Section: Introductionsupporting
confidence: 60%
“…They do not get the concept. It is in line with [4], [9] about the physics test higher order thinking skills development, stated that students creative thinking was categorized as poor. This study aimed to determine the increase in students' higher order thinking skills (HOTS) in physics learning and how the effect of using Synectic learning models on physics learning in high school.…”
Section: Introductionsupporting
confidence: 60%
“…The relevant research was the development of CAT for assessing problem-solving skills conducted by [24]. The results obtained found that tests developed using CAT were effective to apply.…”
Section: Introductionmentioning
confidence: 99%
“…Third, Students' HOTS ability demonstrates that the abilities of problem-solving and creative thinking were in the middle category. Research of Istiyono, Dwandaru, and Faizah (2018) showed that it is not too satisfying students' skills in problem-solving, of which about 36% of students have moderate ability and other students have the low capacity in problemsolving. Based on the findings of this research, the selection of instructional design and assessment that can optimize students' problem-solving ability is essentially implemented for students accustomed to thinking critically and able to provide various solutions to problems encountered.…”
Section: Discussionmentioning
confidence: 99%